Phylogenetic analysis of zoonotic Echinococcus granulosus sensu stricto in humans and domestic animals from Armenia and Türkiye - Saarma, Urmas; Parn, Maris; Atoyan, Hripsime; Laurimae, Teivi; Simsek, Sami; Celik, Figen; Anijalg, Liina (Cambridge Univ Press, 2026)
Cystic echinococcosis (CE) is a zoonotic disease of high public health and economic importance. The disease is caused by various tapeworm species belonging to the Echinococcus granulosus sensu lato species complex. Among these, E. granulosus sensu stricto (genotypes G1 and G3) is the most common cause of human CE worldwide. The aim of this study was to analyse the genetic diversity and phylogenetic relationships of G1 and G3 isolates from Armenia and T & uuml;rkiye, where CE has long been recognized as a significant public health concern. A large portion of the mitochondrial genome (11 675 bp) was sequenced for 85 parasite samples: 47 from T & uuml;rkiye and 38 from Armenia. Samples originated from humans, sheep and cattle. For a global phylogenetic analysis, sequences from previous studies were included, yielding 280 G1 sequences and 55 G3 sequences from various host species and countries worldwide. The main results of this work revealed (i) high genetic diversity of G1 in Armenia and T & uuml;rkiye; (ii) high genetic diversity of G3 in Armenia, whereas only a few representatives of G3 were detected in T & uuml;rkiye; (iii) the subdivision of isolates of G1 and G3 from Armenia and T & uuml;rkiye into several haplogroups; (iv) the dispersion of G1 and G3 haplotypes from Armenia and T & uuml;rkiye across different haplogroups in global phylogenetic networks; and (v) the diffusion routes of G3 isolates from T & uuml;rkiye to Armenia, from Iran to Armenia and from Iran to Greece. These findings highlight the importance of mitogenome analysis for monitoring the spread of CE among animals and humans.
Keywords: Cystic Echinococcosis; Genotype G1; Genotype G3; Mitochondrial Genome; Zoonoses; Zoonotic